BARITAN TRADITION: A CULTURAL AND HUMAN RELATIONSHIP IN FORMING ECO-SPIRITUALITY IN WONODADI COMMUNITY BLITAR - Umi Hanik; A Zahid; Muhamad Hijazi; Shofia Qothrun Nada (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Baritan Tradition is defined by the people of Wonodadi Blitar, as a form of gratitude to God for what has been given to them in the form of an abundant harvest. The harvest as a symbol of soil fertility and the safety of the life of the Wonodadi people as a form of blessing. Baritan Tradition with the takir plontang symbol means that protecting nature is the duty of humans to be stable in carrying out life. This research is a qualitative research with a phenomenological approach, in order to make it easier to identify a community phenomenon based on individual experiences in the community, data obtained from observations, interviews by focusing on the Wonodadi Blitar community with predetermined criteria and supported by the study of Sociology of Religion in order to strengthen one analysis of culture, society and religion. As for the results of the first analysis, there is a function of the relationship between humans and culture which is seen in the form of preserving baritan as a forum for friendship between people. Second, there is an awareness of the community's eco-spirituality by protecting nature, natural products, and the takir plontang as a manifestation of God's existence in maintaining safety in the process of planting until the results are abundant and blessed.